2021
DOI: 10.3390/cancers13143514
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and Ethical Barriers to Cancer Treatment in Nursing Homes and Educational Strategies: A Scoping Review

Abstract: (1) Background: The aging of the population, the increase in the incidence of cancer with age, and effective chronic oncological treatments all lead to an increased prevalence of cancer in nursing homes. The aim of the present study was to map the cultural and ethical barriers associated with the treatment of cancer and educational strategies in this setting. (2) Methods: A systematic scoping review was conducted until April 2021 in MEDLINE, Embase, and CINAHL. All articles assessing continuum of care, paramed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Overcoming these obstacles in cancer therapy necessitates a comprehensive approach including improved access to healthcare, early detection efforts, research funding, and strategies to reduce healthcare disparities. The ongoing progress in cancer research and treatment modalities provides optimism for surmounting these barriers and enhancing cancer patient outcomes. …”
Section: Types Of Cancer Vaccines: a Comprehensive Overviewmentioning
confidence: 99%
“…Overcoming these obstacles in cancer therapy necessitates a comprehensive approach including improved access to healthcare, early detection efforts, research funding, and strategies to reduce healthcare disparities. The ongoing progress in cancer research and treatment modalities provides optimism for surmounting these barriers and enhancing cancer patient outcomes. …”
Section: Types Of Cancer Vaccines: a Comprehensive Overviewmentioning
confidence: 99%
“…6 This includes difficulty with symptom control (partly due to limited pain management skills) and ineffective resident care (due to staff shortages, a lack of skilled symptom control, or conflict within the healthcare team). 6 Inconsistencies also exist between the oncologists' treatment plan and its feasibility within the PALTC setting. As many as 20% of PALTC residents with cancer receive targeted agents and radiation, as these treatments are not typically limited by compromised physical function.…”
Section: Paltc Facility Barriersmentioning
confidence: 99%
“…PALTC staff are frequently unfamiliar with current standards of cancer care, including how best to provide patient‐centered services throughout the admission. Studies from Norway cite lack of awareness of the PALTC nurse's role in cancer care and staffs' fear and resistance to cancer treatment as potential barriers that this population can experience 6 . This includes difficulty with symptom control (partly due to limited pain management skills) and ineffective resident care (due to staff shortages, a lack of skilled symptom control, or conflict within the healthcare team) 6 …”
Section: Systematic Barriersmentioning
confidence: 99%
“…6 This may also lead to questions about how to validate treatment decisions in cognitively impaired people and how to collect consent from the person and his/her family. [16][17][18] A recent scoping review 19 found many factors interfering with the decision to investigate and treat, leading to late or unstaged disease, palliative-oriented care instead of curative, and a higher risk of unjustified transfers to acute care settings.…”
Section: Introductionmentioning
confidence: 99%